(untitled) (Journal of Social Sciences Review, 2023)
Portfolio assessment has emerged as an alternative technique of assessment of students due to its noteworthy role in enhancing students’ achievement. Therefore, the present study was an attempt to develop a portfolio and further investigate the role of portfolio assessment on students’ achievement at the secondary school level students. Pupils of the ninth class were considered as the population of the research study. Two groups of ninth-class students (Control Group and Experimental Group) from a public school located in Multan were treated as a sample of the study. The targeted population consisted of 73 students. The control group students (N=42) were assessed through traditional assessment techniques, whereas the experimental group (N=31) received treatment (portfolio assessment strategy). Data were collected through the results of the first-term examination, second-term examination, third-term examination and monthly tests from September to December. All tests and results were saved in their portfolios, and later on, their achievement was assessed on the basis of recorded information in a portfolio. Test scores and self-reporting questionnaire scores were used as measures of students’ academic achievements and mean The percentage of the experimental group was 67.3%, while the control group got 52.3%. There was no significant difference between the experimental and control groups for the first term and a significant difference for the third term.